Observasi Tingkat Ketertarikan Anak Terhadap Video Klip Animasi 2D Lagu Daerah di Indonesia - Riwinoto - Muthmainah - Rani Wulansari - Tia Tamita - Elvira Amanda - Selly Artaty Zega (Politeknik Negeri Batam, 2018)
Animation means animate, the attempt to move something that can’t move. Making animations can be performed using Luther Sutopo methods, what is divided into six stages, namely Concept, Design, Master Collecting, Assembly, Testing and Distribution. Making the Animation has been done in many countries, so do Indonesian country. Then Animation turned out to have a big hand in folk song to children. And attract children to learn more about Indonesia, especially for Yogyakarta folk song.